Leukocytosis as a Predictor of Clinical Worsening and Complications in Children with Pertussis: A Systematic Review of Case Study - Bakhtiar Bakhtiar; Inayah Zhiaul Muttaqin; Ghazi Maulana; Ghina Tsurayya; Garsia Safana (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Pertussis is a highly contagious disease with clinical features ranging from mild to severe and various complications. Hematological examination, especially the leukocyte count, can predict the possibility of clinical deterioration with several complications, such as pneumonia. This case study aimed to assess whether leukocytosis could indicate the clinical worsening of pertussis in children. This research method is a systematic review on a case study. The subject of this case study is a child with pertussis experiencing clinical deterioration. Prominent laboratory data in this case study includes leukocytosis. This systematic review aims to analyze the association between leukocytosis and the clinical deterioration of this case study. Literature search procedure using PubMed, Cochrane, and Google Scholar search instruments. The keywords used are "pertussis," "risk factor," and "and children." Using the limitations of randomized controlled clinical trials, systematic reviews, meta-analyses, cohorts, and cross-sectional or case series, the language of instruction is English, and publications within the last 20 years. Overall, 16,666 articles were obtained, consisting of 43 pieces from PubMed; only two papers were valid. Of the 3,123 articles on the Cochrane, only two are valid. Likewise, out of 13,500 articles on Google Scholar, only two are valid. Furthermore, it was traced based on the aspect of duplication, then three papers were found, which were cohort studies. It was concluded that leukocytosis predicts clinical deterioration and complications in children with pertussis.